فعالية لعبة JMATCH في تطبيق HOT POTATOES لترقية مفردات لدى الطلاب الصف السابع بمدرسة المتوسطة الإسلامية نهضة الوطن الدينية الإسلامية تمبنج فوتيك - Aini, Nurul; Watul Fitri, Widya (Lughatu Ad-dhat, 2024)
Vocabulary is the first thing that influences the way humans speak, when humans know a lot of vocabulary it can support their language skills. Based on observations made by researchers at MTs NWDI Tembeng Putik regarding the problems of learning Arabic, lack of mastery of vocabulary, so learning techniques are needed that can increase students' vocabulary. The aims of this research are: To find out how to apply the jmatch game on the hot potatoes application to increase the vocabulary of class VII students at MTs NWDI Tembeng Putik and To find out the effectiveness of the jmatch game on the hot potatoes application to increase the vocabulary of class VII students at MTs NWDI Tembeng Putik. In this research the author uses a quantitative approach with an experimental type of research. The data collection techniques used are observation, tests and documentation. The results of this research are : 1) the application of the jmatch game in the hot potatoes application to increase vocabulary begins by asking students questions according to the learning theme, and students answer these questions directly in the hot potatoes application by matching arabic vocabulary with its meaning and arabic vocabulary with arabic in the form of answers to arabic conversations in the applicarion. 2) the effectiveness of the jmatch game on the hot potatoes application to increase students vocabulary is known from the result of the t-test which shows that the results of t-count > t-table 4,471 > 1,686. Then Ha is accepted and Ho is rejected. Thismeans that the jmatch game on the hot potatoes application is effective in increasing vocabulary.